2016
DOI: 10.1016/j.trd.2016.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Development of driving cycles for electric vehicles in the context of the city of Florence

Abstract: This document is the accepted version of the article "Development of driving cycles for Electric Vehicles in the context of the city of Florence", to be used for sharing through Author Institution repository.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(40 citation statements)
references
References 54 publications
0
37
0
Order By: Relevance
“…These configurations result in either confined flows with one or more moving boundaries, or free surface flows supported by at least one substrate/base. Extensive physical and numerical studies have illustrated the profound impact of these boundary conditions to the overall flow behavior in both two-dimensional (2D) and three-dimensional (3D) situations [2,[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. For instance, Pouliquen [8] found that base roughness is the key to the minimum thickness necessary to sustain a steady flow at a given inclination, and proposed a scaling law correlating this thickness with the mean flow velocity.…”
Section: Introductionmentioning
confidence: 99%
“…These configurations result in either confined flows with one or more moving boundaries, or free surface flows supported by at least one substrate/base. Extensive physical and numerical studies have illustrated the profound impact of these boundary conditions to the overall flow behavior in both two-dimensional (2D) and three-dimensional (3D) situations [2,[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. For instance, Pouliquen [8] found that base roughness is the key to the minimum thickness necessary to sustain a steady flow at a given inclination, and proposed a scaling law correlating this thickness with the mean flow velocity.…”
Section: Introductionmentioning
confidence: 99%
“…e results indicated that the characteristics of the proposed driving cycle were able to represent the aggressive driving of the real-world well compared to existing standard driving cycles. Similar studies were also carried out in Dublin by Brady and O'Mahony [5], in Florence by Berzi et al [30], and in Southeast Michigan by Lee et al [31]. It had also found that the role of a typical driving cycle was increasingly significant, not only for vehicle certification and design but also for analyzing the impact of PHEV on the grid.…”
Section: Introductionmentioning
confidence: 63%
“…The k-means algorithm has been widely used in cluster computing in the existing literature [3,4,19,24,43]. The k-means clustering algorithm uses the Euclidean distance between a sample and cluster center as a criterion for similarity determination, and it has the advantages of efficiency and simplicity [19,43].…”
Section: Clustering Based On the K-means And Svmmentioning
confidence: 99%
“…Hence, it is necessary to develop a unique driving cycle for each typical city and region. Moreover, many researchers have found that the energy consumption of an EV for a real-world driving cycle greatly differs from that based on the international standard driving cycles [19,[22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%